Pengaruh Faktor Emosional dan Faktor Rasional Terhadap Keputusan Pedagang dalam Menggunakan Jasa Perbankan Syariah: Studi Kasus pada Pedagang Kecamatan Serbajadi Kabupaten Serdang Bedagai - Muliyani, Rahmi; Pradesyah, Riyan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to identify emotional factors and rational factors of traders in Serbajadi District, Serdang Bedagai Regency when making decisions in using Islamic Banking services. This study used a quantitative approach with the distribution of questionnaires. The sample was randomly selected using proportional random sampling method and Slovin algorithm with a total of 88 traders. The data obtained were processed using the SPSS 27 application and multiple linear regression analysis methods used. The results obtained partially, the emotional factor variable (X1) has a negative and significant effect on the decision of Traders (Y) in using Islamic banking services. And the rational factor variable (X2) has an influence and is significant on the decision of traders (Y) in using Islamic banking services. Simultaneously, emotional factors (X1) and rational factors (X2) influenced traders' decisions (Y) in using Islamic banking services, amounting to 58.8% and other factors not included in the research model impacted the remaining 41.2%.